Modern Health Service Utilization and Associated Factors among Adults in Southern Ethiopia. (11th January 2021) - Bitew Workie, Shimelash; Mekonen, Niguse; Michael, Mulugeta W.; Molla, Getahun; Abrha, Solomon; Zema, Zewde; Tadesse, Takele
Abstract : Background . The Ethiopian government is striving to improve the health status of its population through the expansion and strengthening of primary health care services in both rural and urban settings of the country. The study aimed to measure modern health service utilization and associated factors in Wolaita Sodo town, Ethiopia. Method . A cross-sectional study design was implemented from May to June 2019 in Wolaita Sodo town, Ethiopia. All 786 study participants were selected by multistage systematic random sampling. Data were collected by face-to-face interviews using a pretested structured questionnaire. Data were collected by an open data kit. Stata window version 15.0 was also employed for statistical analysis. Multiple logistic regression was conducted, and a 95% confidence interval was considered for interpretation. Result . Health service utilization was 77.2% with (95% CI of 74.1%, 80.0%). In terms of health facilities in which they visit, first 50.6% were at the public health center and 25.5% of them were at Teaching and Referral Hospital. Respondents with marital status married and widowed have higher odds of utilizing health services compared to single marital status (AOR: 2.96; 95% CI: 1.7–5.2 and 9.0; 95% CI: 1.69–48.0), respectively. Respondents with middle and highest wealth status have higher odds of health service utilization than poor wealth status with AOR (1.75 95% CI 1.03–2.97 and 1.58 95% CI; 1.01, 2.77). Similarly, respondents who had chronic disease and perceived poor health status have higher odds of health service utilization. Conclusion . Modern health services utilization was found to be unsatisfactory. Being married, wealth status being middle and high, having chronic health conditions, and having poor perceived health status were found to have a statistically significant association with health service utilization.